Penerapan Terapi Rehabilitasi Kemandirian Activity Of Daily Living (ADL) pada Pasien Skizofrenia di Rumah Sakit Jiwa Daerah Provinsi Lampung - Cahyaningsih, Eka Ayu; Citra, Okta Widya Misma; Putra, Ardi Pramudya Eka (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Schizophrenia patients often see impaired basic abilities, such as Activities of Daily Living (ADL). ADL training can increase independence in client self-care. The aim of this final scientific work is to explain the effect of rehabilitation therapy on activities of daily living in schizophrenia patients. This final scientific work uses the pre-test and post-test method of a case experimental study regarding the application of the effect of ADL independence rehabilitation therapy in schizophrenia patients. The population in the final scientific work were schizophrenic clients with the main problem being a stable self-care deficit of 2 patients. This final scientific activity was carried out from 07 to 14 April 2023. The intervention provided was ADL independence rehabilitation therapy. The data collection techniques used were interviews, observation, and questionnaires based on the Barthel ADL Index. The results of helping schizophrenic patients with the main problem of self-care deficit using ADL independence rehabilitation therapy have proven to be effective in increasing ADL patient independence. Based on the results obtained before carrying out ADL independence rehabilitation therapy, the average score for signs and symptoms of ADL independence was 42.42% and after carrying out ADL independence therapy, the average score for signs and symptoms of ADL independence increased to 57.57%. It is expected to always be able to unite and invite clients to increase ADL clients. It can be concluded that there is an increase in ADL independence, which shows that ADL rehabilitation interventions can help increase respondents' independence in self-care. It is expected to always be able to unite and invite clients to increase ADL clients. Keywords: Activities of Daily Living,Schizophrenia, Rehabilitation  ABSTRAK Penderita skizofrenia sering kali mengalami gangguan kemampuan dasar, misalnya Activity of Daily Living (ADL). Pelatihan ADL dapat meningkatkan kemandirian dalam perawatan diri klien. Tujuan dari karya ilmiah akhir ini adalah untuk menjelaskan pengaruh terapi rehabilitasi terhadap aktivitas kehidupan sehari-hari pada pasien skizofrenia. Karya ilmiah akhir ini menggunakan metode pre-test dan post-test studi kasus eksperimental mengenai penerapan pengaruh terapi rehabilitasi kemandirian ADL pada pasien skizofrenia. Populasi dalam karya ilmiah akhir ini adalah klien skizofrenia dengan masalah utama defisit perawatan diri yang stabil sebanyak 2 pasien. Kegiatan ilmiah akhir ini dilaksanakan pada tanggal 07 hingga 14 April 2023. Intervensi yang diberikan adalah terapi rehabilitasi kemandirian ADL. Teknik pengumpulan data yang digunakan adalah wawancara, observasi, dan kuesioner berdasarkan Barthel ADL Index. Hasil penelitian diperoleh intervensi ini dapat membantu pasien skizofrenia dengan masalah utama defisit perawatan diri dengan menggunakan terapi rehabilitasi kemandirian ADL terbukti efektif meningkatkan kemandirian pasien ADL. Berdasarkan hasil yang diperoleh sebelum dilakukan terapi rehabilitasi kemandirian ADL rata-rata skor tanda dan gejala kemandirian ADL sebesar 42,42% dan setelah dilakukan terapi rehabilitasi kemandirian ADL rata-rata skor tanda dan gejala kemandirian ADL meningkat menjadi 57,57%. Diharapkan untuk selalu bisa menyatukan dan mengajak klien untuk meningkatkan ADL klien. Dapat disimpulkan terdapat peningkatan kemandirian ADL yang menunjukkan bahwa intervensi rehabilitasi ADL dapat membantu meningkatkan kemandirian responden dalam perawatan diri. Diharapkan untuk selalu bisa menyatukan dan mengajak klien untuk meningkatkan ADL klien. Kata Kunci: Aktivitas Sehari-Hari, Skizofrenia, Rehabilitasi